2013
DOI: 10.1088/0004-6256/145/5/141
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Circumstellar Disks of B-Type Stars With Observations From the Palomar Testbed Interferometer

Abstract: Geometrical (uniform disk) and numerical models were calculated for a set of B-emission (Be) stars observed with the Palomar Testbed Interferometer (PTI). Physical extents have been estimated for the disks of a total of 15 stars via uniform disk models. Our numerical non-LTE models used parameters for the B0, B2, B5, and B8 spectral classes and following the framework laid by previous studies, we have compared them to infrared K-band interferometric observations taken at PTI. This is the first time such an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Both found only small deviations from circular symmetry in the disc, suggesting the system is seen close to pole-on; Quirrenbach et al (1997) found an axial ratio of 0.95±0.22, from which the minimum inclination angle is 18 • , while Tycner et al (2005) found the axial ratio to be 0.75±0.05, implying a minimum inclination angle of 41 • . Grzenia et al (2013) found a much smaller angular extent of the disc in K band observations from the Palomar Testbed Interferometer, of only 0.71±0.01 mas, although it must be noted that they fit only a single uniform disc component to their observations, and it seems likely the measurement was dominated by the central star. Touhami et al (2013) were unable to resolve the disc in K band with the CHARA Array.…”
Section: Alcyonementioning
confidence: 84%
“…Both found only small deviations from circular symmetry in the disc, suggesting the system is seen close to pole-on; Quirrenbach et al (1997) found an axial ratio of 0.95±0.22, from which the minimum inclination angle is 18 • , while Tycner et al (2005) found the axial ratio to be 0.75±0.05, implying a minimum inclination angle of 41 • . Grzenia et al (2013) found a much smaller angular extent of the disc in K band observations from the Palomar Testbed Interferometer, of only 0.71±0.01 mas, although it must be noted that they fit only a single uniform disc component to their observations, and it seems likely the measurement was dominated by the central star. Touhami et al (2013) were unable to resolve the disc in K band with the CHARA Array.…”
Section: Alcyonementioning
confidence: 84%
“…The emission lines are recombination lines that occur in a geometrically thin, equatorial, circumstellar disk, according to a model first proposed by Struve (1931). The model has been modified and further developed by many authors and recently confirmed by direct interferometric observations (Quirrenbach et al 1997;Gies et al 2007;Carciofi et al 2009;Grzenia et al 2013). The disk may entirely disappear and re-appear unpredictably.…”
Section: Introductionmentioning
confidence: 99%
“…These models have also been able to reproduce the observed correlation seen between Hα and long term variations in visual magnitude, which are interpreted as formation and dissipation of the disk over a long periods of time in Classical Be stars (Sigut & Patel 2013). Observed IR line fluxes Halonen et al 2008) as well as optical and near-IR interferometry (Jones et al 2008;Tycner et al 2008;Mackay et al 2009;Grzenia et al 2013;Sigut et al 2015) computed with Bedisk and Beray models, have been used to put constraints on the several Classical Be star disks.…”
Section: Classical Be Stars and The Beray And Bedisk Codesmentioning
confidence: 95%